Characterization of Patterned Porous Low-k Dielectrics: Surface Sealing and Residue Removal by Wet Processing/Cleaning. (1st January 2016) - Le, Q. T.; Kesters, E.; Decoster, S.; Chan, B. T.; Nguyen, M. P.; Conard, T.; Vanleenhove, A.; Holsteyns, F.; De Gendt, S.
Abstract : The results described in this paper first demonstrate key differences between a plasma-exposed blanket porous dielectric sample and a patterned structure in terms of surface sealing induced by the patterning plasma using ellipsometric porosimetry characterization. While the blanket CVD organosilicate glass (nominal k -value = 2.4, ∼20% of porosity) surface was sealed by the C4 F8 /CF4 -based plasma, the surface of the analogous patterned structure of 45 nm 1/2 pitch was found to be completely open after the same patterning plasma process. Second, the surface composition of the patterned feature, type of the residues generated during the plasma etch, and the effect of a subsequent wet clean step are presented. The experimental results demonstrate that the use of a relevant patterned test structure and its characterization represent an appropriate approach for the optimization of the etch and cleaning processes. The removal efficiency of various wet clean solutions, including dilute HF, citric acid, tetramethylammonium hydroxide:H2 O2 :H2 O mixture, and a slightly alkaline formulated mixture, with regard to polymer residues, CFx, and metal-containing residues, TiFx, can be clearly distinguished using the patterned porous low- k stack.